Examining the influence of electrosynthesis conditions on the composition of tin-oxide catalyst - Vargalyuk, Victor; Plyasovskaya, Kateryna; Sknar, Irina; Cheremysinova, Anna; Sigunov, Oleksii; Sverdlikovska, Olga (Eastern-European Journal of Enterprise Technologies, 2017)
Tin dioxide can serve as an active material in micro- and optoelectronics, energy generation, and catalysis. Its synthesis method is determined by the scope of its application. We established regularities in the electrochemical synthesis of a catalytically-active oxide mixture on the surface of tin in alkaline solutions. By employing the original coulometric method we determined quantitative composition of the electrochemically-obtained oxide films in a wide range of formation potentials. At an electrode potential of ‒0.3, the molar ratio of Sn(II)/Sn(IV) is equal to unity. Based on the analysis of processes that might occur under the specified conditions of electrosynthesis, it can be assumed that the surface of tin is coated with a thin layer of SnSnO3. Amorphous nature of the electrode surface, passivated at ‒0.3 V, indirectly confirms this assumption. At a potential of 3.0 V, the oxide film’s content of Sn(IV) is 59 % (mol), Sn(II) ‒ 41 % (mol). Consequently, the film contains 18 % (mol) of SN(IV), which is not included in the composition of SnSnO3. In other words, active tin dioxide is formed exactly at such a potential. Catalytic activity of the obtained materials is demonstrated on the example of methyl tert-butyl ether electrooxidation. The starting concentration of MTBE on the tin electrode, oxidized at 3.0 V, is reduced by 98 % within 180 minutes, while only 73 % of MTBE is decomposed over the same time on a nickel electrode.